Linking employer branding and internal branding: establishing perceived employer brand image as an antecedent of favourable employee brand attitudes and behaviours. Issue 4 (26th October 2018) - Hoppe, Daniel
Abstract : Purpose: The purpose of this paper is to establish the symbolic facet of perceived employer brand image (PEBI) as an antecedent of favourable brand-related identification and employee behaviours, namely, corporate brand identification (CBI) and brand citizenship behaviours (BCB). Design/methodology/approach: A standardized questionnaire was used. Data collection occurred at a maximum care hospital in Germany ( N = 366). Structural equation modelling was used in the data analysis. Findings: A direct link between PEBI and BCB was theoretically derived from social exchange theory and could be empirically confirmed. In addition to a direct relationship, a mediated relationship based on social identity theory was outlined. PEBI influences BCB via CBI. The mediated pathway accounts for 70 per cent of the variance. Practical implications: Understanding the impact of symbolic job offerings on favourable brand-related employee attitudes and behaviours should lead practitioners to focus on increasing employees' perceptions of the employer's prestige and sincerity, for example, by strengthening employee target group-oriented communications about corporate social responsibility or increasing out-group salience when communicating organizational achievements. Originality/value: This paper transfers the concept of organizational attractiveness, organizational identification and favourable employee behaviours to a corporate brand focus. It is the first integration of the symbolic dimension of the instrumental-symbolic framework in an internal branding context.